Peningkatan Pengetahuan Kesehatan dan Skrining Hiperuricemia Pada Guru SMA Muhammadiyah 11 Jakarta - Ratih Kartika Dewi; Engla Merizka (FKM UIN Sumatera Utara Medan, 2024)
Healthy people have greater opportunities to play an active role in the development of the nation and state, for example people who work as teachers. Teachers who are physically and mentally healthy can certainly play a strong role in creating a positive culture in the school environment. Currently, Tachers pay little attention to their health due to the heavy workload, therefore it is necessary to provide information and counseling to increase knowledge of health and degenerative diseases such as gout. The aim of this community service activity is to increase the knowledge of teachers at SMA Muhammadiyah 11 Jakarta about hyperuricemia and carry out hyperuricemia screening through checking uric acid levels as an early detection of gouty arthritis. The method used is an interactive lecture and to check uric acid levels using the Point of Care Testing (POCT) method. The results of data analysis showed that there was a significant difference between before and after being given health education related to hyperuricemia among teachers at SMA Muhammadiyah 11 Rawamangun Jakarta (p<0.05) with a mean before being given education of 65 versus 83. Uric acid levels test showed a higher prevalence of hyperuricemia female teachers are 59%, while male teachers are 44%.